Visual Reaction Time™ as a Predictor of Sexual Offense Recidivism. (April 2015) - Gray, Steven R.; Abel, Gene G.; Jordan, Alan; Garby, Tina; Wiegel, Markus; Harlow, Nora
In this study, we investigated the use of Visual Reaction Time™ (VRT™) for sexual interest in children to predict recidivism of sexual offenses among men who sexually abused children and men with other sexually deviant behaviors. The authors hypothesized that study participants with a higher VRT™ to stimuli of children would be more likely to sexually reoffend compared with those with a lower VRT™ to stimuli of children. Participants included 621 adult males on parole or probation for acting on a range of sexual paraphilias who sought outpatient treatment or evaluation at two separate therapists' practices. Sample 1 consisted of 284 adult males followed up (by the lead author) during a 15-year period, while Sample 2 consisted of 337 adult males followed up (by the second author) during a 7-year period. A discrete-time hazard model found VRT™ to children to be significantly related to sexual recidivism. The researchers found that VRT™ to children measured at intake held up in its predictive ability over a 15-year period. When the participants were divided into three groups based on their VRT™, of the 97 participants who measured at least one standard deviation lower than the mean VRT™, 0% reoffended. The 432 participants in the medium-VRT™ group had an estimated recidivism rate of 7% after 15 years and the 92 participants who measured at least one standard deviation higher than the mean had an estimated recidivism rate of 27%.